2018
DOI: 10.12681/jhvms.16049
|View full text |Cite
|
Sign up to set email alerts
|

Acute phase proteins and biochemical and oxidative stress parameters in Hypoderma spp. infested cattle

Abstract: ABSTRACT. The aim of the present study was to determine concentrations of acute phase proteins (APP), oxidative stress and some biochemical parameters in naturally infested cattle with Hypoderma spp. For this purpose, 10 clinically healthy cattle as controls and 25 Brown Swiss cattle with Hypoderma spp. were used. Blood samples were collected to tubes from jugular vein. Parts of blood samples were stored without any process as a whole blood. The serum was separated from the remaining blood samples. The reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…A second increase in Hp levels was detected at approximately 22 and 35 dpi in the intravenously and intradermally inoculated groups, respectively, which may be related to a delay in seroconversion in both groups and the higher severity of clinical signs observed in the intradermally infected group. According to the concentration of Hp, both the subcutaneously and intradermally infected groups presented higher Hp concentrations of 1–2 g/l, while Hp levels were lower in the intravenously infected group (between 0.2–1 g/l), probably related to the severity of the infection, as stated by others [ 25 , 26 ]. In fact, there are several examples of the diagnostic and prognostic value of serum Hp in mastitis, enteritis, peritonitis, pneumonia, endocarditis and endometritis in cattle [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…A second increase in Hp levels was detected at approximately 22 and 35 dpi in the intravenously and intradermally inoculated groups, respectively, which may be related to a delay in seroconversion in both groups and the higher severity of clinical signs observed in the intradermally infected group. According to the concentration of Hp, both the subcutaneously and intradermally infected groups presented higher Hp concentrations of 1–2 g/l, while Hp levels were lower in the intravenously infected group (between 0.2–1 g/l), probably related to the severity of the infection, as stated by others [ 25 , 26 ]. In fact, there are several examples of the diagnostic and prognostic value of serum Hp in mastitis, enteritis, peritonitis, pneumonia, endocarditis and endometritis in cattle [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 52%
“…According to the concentration of Hp, both the subcutaneously and intradermally infected groups presented higher Hp concentrations of 1–2 g/l, while Hp levels were lower in the intravenously infected group (between 0.2–1 g/l), probably related to the severity of the infection, as stated by others [ 25 , 26 ]. In fact, there are several examples of the diagnostic and prognostic value of serum Hp in mastitis, enteritis, peritonitis, pneumonia, endocarditis and endometritis in cattle [ 25 , 26 ]. However, Hp values did not significantly vary in naturally infected animals despite the severity of the infection, particularly in bulls with early acute infection [ 6 ].…”
Section: Discussionmentioning
confidence: 52%
“…In parasite infections, the host organism forms a response mechanism against parasites by means of free radicals that cause oxidative stress (Woodbury et al 1984). There are many studies showing that oxidative stress occurs in animals infected with the parasite (Simsȩk et al 2006, Saleh 2008, Saleh et al 2009, Merhan et al 2017a, Bozukluhan et al 2017, Gültekin et al 2017, Kozan et al 2010). In our study, it was observed that oxidative stress increased clearly by increasing TOS and OSI values in acute coccidiosis in kids.…”
Section: Discussionmentioning
confidence: 99%
“…Haptoglobin has been reported to be present in very low concentrations (<0.1 mg/mL) in healthy animals. But its concentrations increase and remain high in many bacterial, viral, parasitic and inflammatory diseases as long as the stimulus persists [7,[25][26][27][28] . It is a nonspecific marker of tissue damage, and suggested to be used to determine prognosis and severity of the diseases.…”
Section: Discussionmentioning
confidence: 99%